Effectiveness and Safety of Acupuncture for Migraine: An Overview of Systematic Reviews. (23rd March 2020) - Li, Yu-Xi; Xiao, Xi-li; Zhong, Dong-Ling; Luo, Liao-Jun; Yang, Han; Zhou, Jun; He, Ming-Xing; Shi, Li-Hong; Li, Juan; Zheng, Hui; Jin, Rong-Jiang
Abstract : Background . Migraine is a common neurological disease, which burdens individuals and society all over the world. Acupuncture, an important method in Traditional Chinese Medicine, is widely used in clinical practice as a treatment for migraine. Several systematic reviews (SRs) have investigated the effectiveness and safety of acupuncture for migraine. Objective . To summarize and critically assess the quality of relevant SRs and present an objective and comprehensive evidence on the effectiveness and safety of acupuncture for migraine. Data Sources . MEDLINE, Embase, Cochrane Library, PROSPERO database, Chinese National Knowledge Infrastructure (CNKI), Chinese Biological Medicine (CBM), China Science and Technology Journal (SCTJ), and WanFang database (WF) were searched from inception to December 2019 and grey literatures were manually searched. Selection Criteria . SRs which meet the criteria were independently selected by 2 reviewers according to a predetermined protocol. Data Extraction . Characteristics of included SRs were independently extracted by 2 reviewers following a predefined data extraction form. Review Appraisal . The methodological quality, risk of bias, and reporting quality of included SRs were assessed, respectively, by a Measurement Tool to Assess Systematic Reviews (AMSTAR) 2, the Risk of Bias in Systematic reviews (ROBIS) tool, and the Preferred Reporting Item for Systematic Review and Meta-analysis-Acupuncture (PRISMA-A) statement. The quality of outcomes was evaluated by the Grading of Recommendations Assessment, Development, and Evaluation (GRADE). Results . A total of 15 SRs were included. All the SRs were published between 2011–2019. Based on AMSTAR 2, 14 out of 15 SRs were rated critically low quality and 1 was rated low quality. According to ROBIS tool, 9 SRs (60%) were low risk of bias. With the PRISMA-A checklist, we found 11 out of 15 SRs were found adequately reported over 70%. With the GRADE tool, we found high quality of evidence indicated that the effective rate of acupuncture was superior to western medicine in treatment of migraine. Besides, acupuncture reduced more headache days and the times of using painkiller and was more effective in reducing the frequency and degree of headache than western medicine and sham acupuncture. Limitations . There might be some missing information. The accuracy of the conclusions may be decreased reduced since we were unable to synthesis all the evidence. Conclusions . Based on high quality of evidence, we concluded that acupuncture may be an effective and safe therapy for migraine. However, the quality of SRs in acupuncture for migraine still needs more improvement.